Presentation, Evaluation and Treatment of Urinary Bladder Tumour - Abdullah, A B M; Rahman, Md Mizanur; Karim, Shoibul; Anwar, Shahed Mohammed; Khan, Hussain Ahammed; Rahman, Md Tanvir; Afrose, Roksana (IAHS Medical Journal, 2025)
Background: Bladder carcinoma is the most common urological malignancy in Bangladesh. Nevertheless, the common presentations of the patient and their ongoing management system are yet to be evaluated. This study aimed to determine the clinicopathological characteristics of histologically confirmed bladder carcinoma at a tertiary care hospital of Dhaka, Bangladesh. Materials and methods: This was a cross sectional study. A total of 50 patients of bladder carcinoma were included in this study from the Department of Urology, Dhaka Medical College Hospital during May, 2017 to October, 2017. All patients were evaluated with regards to clinical presentation, cystoscopic findings and histopathological data. Results: The mean age was 63.78±9.79 years (Age range: 27-88 years) and 78% were male. Hematuria was manifested by 31(62%), 28% and 32%, respectively, showed urinary frequency and urgency and 22% patients were asymptomatic. Maximum 52% presented at T2 (T2 . 5 year survival , 50-80% patients are cured by OT) which was followed by 30% T1a(T1a . superficial muscle layer involvement). 82% had transitional cell carcinoma and rest 18% had non transitional cell carcinoma. Among the later varieties of bladder cancer, Squamous cell carcinoma was the highest - 10%. Conclusion: Bladder cancer has a varied spectrum of presentation and patients admitted in the hospitals generally have a higher stage and grade of disease. IAHS Medical Journal Vol 7(2), December 2024; 25-29